TYPES AND FUNCTIONS OF ASSOCIATIVE MEANINGS IN THE OPENING STATEMENTS USED BY THE HOST OF MATA NAJWA TALK SHOW - Nelvia Nelvia; Rusdi Noor Rosa; Fitrawati Fitrawati (Universitas Negeri Padang, 2019)
AbstractThe purpose of this research is to find out the types and the functions of associative meaning in the opening statements used by the host of Mata Najwa Talk Show. This research uses descriptive qualitative research as the research method. Data of the research are words, phrases, and sentences that contain associative meaning. This research uses the theory conducted by Leech (1974) to find out the types of associative meaning, and the theory proposed by Searle (1979) to find out the functions of associative meaning. The result shows that the types of associative meaning in this research are connotative meaning (25 data), stylistic meaning (1 data), affective meaning (5 data), reflected (21 data), and collocative meaning (0 data). This research also find out the functions of associative meaning; connotative meaning is used to assert the hearer about the speaker’s ideas; stylistic meaning is used to show the expression of the speaker, expressed through the style of the use of words, affective meaning is used to express the feeling of the speaker; reflected meaning is used to present the new sense of word. The function of associative meaning in this research mostly used as representative. Key words: Associative Meaning, Opening Statement, Talk Show.